Walking dead: Permeabilization of heat-treated Geobacillus stearothermophilus ATCC 12980 spores under growth-preventing conditions. (June 2017) - Mtimet, Narjes; Trunet, Clément; Mathot, Anne-Gabrielle; Venaille, Laurent; Leguérinel, Ivan; Coroller, Louis; Couvert, Olivier
Abstract: Although heat treatment is probably the oldest and the most common method used to inactivate spores in food processes, the specific mechanism of heat killing of spores is still not fully understood. The purpose of this study is to investigate the evolution of the permeabilization and the viability of heat-treated spores during storage under growth-preventing conditions. Geobacillus stearothermophilus spores were heat-treated under various conditions of temperature and pH, and then stored under conditions of temperature and pH that prevent growth. Spore survival was evaluated by count plating immediately after heat treatment, and then during storage over a period of months. Flow cytometry analyses were performed to investigate the Syto 9 permeability of heat-treated spores. Sub-lethally heat-treated spores of G. stearothermophilus were physically committed to permeabilization after heat treatment. However, prolonged heat treatment may abolish the spore permeabilization and block heat-treated spores in the refractive state. However, viability loss and permeabilization during heat treatment seem to be two different mechanisms that occur independently, and the loss of permeabilization properties takes place at a much slower rate than spore killing. Under growth-preventing conditions, viable heat-treated spores presumably lose their viability due to the permeabilization phenomena, which makes them more susceptible to the action of adverse conditions precluding growth. Highlights: Sub-lethally heat-treated spores are committed to germinate. Dead and viable heat-treated spores could be permeabilized after heat treatment. Extended heat treatment blocks spores in the refractive state. Viability loss and permeabilization are two independent mechanisms.